2011
DOI: 10.2165/11533150-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Morgellons Disease and Delusions of Parasitosis

Abstract: Morgellons disease is a controversial and poorly defined symptom cluster of skin lesions and somatic symptoms, most notably 'fibers' in the skin. Because of widespread coverage in the media and on the Internet, there are an increasing number of patients presenting to dermatologists. We present three patients who believed that they had fibers in their skin. We offer a discussion of delusions of parasitosis to demonstrate similarities between these conditions. It has been suggested by a limited number of healthc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
33
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 35 publications
1
33
0
3
Order By: Relevance
“…The histopathologic and immunohistochemistry analysis revealed nonspecific findings without infectious etiologies. The evidence of the black fiber observed in gross specimen was also absent, which was consistent to previous study5. It could be dissolved by the organic solvents used in the tissue preparation process.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The histopathologic and immunohistochemistry analysis revealed nonspecific findings without infectious etiologies. The evidence of the black fiber observed in gross specimen was also absent, which was consistent to previous study5. It could be dissolved by the organic solvents used in the tissue preparation process.…”
Section: Discussionsupporting
confidence: 91%
“…One study5 disclosed that laboratory values associated with infection were normal in Morgellons disease patients, and that cutaneous biopsy specimens revealed only nonspecific findings. Another research2 from the Centers for Disease Control and Prevention reported that there was no common underlying medical condition or infectious organism in Morgellons disease cases, and that the fibers were composed mainly of cellulose.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no clinical evidence to support infectious aetiology of this condition and the skin biopsies have demonstrated non-specific findings. Patients with this condition often lack insight, hold their beliefs firmly and are resistant to psychiatric treatment 11. Because of recent publicity of Morgellons disease, center for disease control (CDC) is currently investigating this condition.…”
Section: Discussionmentioning
confidence: 99%
“…The role of postsynaptic-D2 receptors (in mediating the anti-psychotics' effect) and the role of fronto-striato-thalamo-parietal brain circuits inmediating Delusional Infestation(DI), which is in the same spectrum asDP, was confirmed. 2,6,[11][12][13][14][15][16] …”
Section: 12mentioning
confidence: 99%